2021
DOI: 10.1136/annrheumdis-2020-219498
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19-related death in people with rheumatic diseases: results from the COVID-19 Global Rheumatology Alliance physician-reported registry

Abstract: ObjectivesTo determine factors associated with COVID-19-related death in people with rheumatic diseases.MethodsPhysician-reported registry of adults with rheumatic disease and confirmed or presumptive COVID-19 (from 24 March to 1 July 2020). The primary outcome was COVID-19-related death. Age, sex, smoking status, comorbidities, rheumatic disease diagnosis, disease activity and medications were included as covariates in multivariable logistic regression models. Analyses were further stratified according to rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
611
7
55

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 591 publications
(712 citation statements)
references
References 32 publications
39
611
7
55
Order By: Relevance
“…In these settings the effects of select immune inhibition early in the course of infection may provide unique opportunities for insights not possible when such agents are not started until the disease progresses. The CGRA is the largest COVID-19 specific registry among IMIDs and has revealed that having a clinically uncontrolled IMID, as well as not receiving immunosuppressive therapy, are risks for severe outcomes [54]. In terms of specific therapies, aside from glucocorticoids, receiving rituximab or sulfasalazine is associated with higher odds of death, compared to methotrexate monotherapy (OR 4.04, 95% CI 2.32-7.03) and (3.60, 1.66-7.78), respectively [54].…”
Section: What Lessons May Be Learned From Examining the Clinical Outcomes Of Patients On Immunomodulatory Therapy At Baseline?mentioning
confidence: 99%
“…In these settings the effects of select immune inhibition early in the course of infection may provide unique opportunities for insights not possible when such agents are not started until the disease progresses. The CGRA is the largest COVID-19 specific registry among IMIDs and has revealed that having a clinically uncontrolled IMID, as well as not receiving immunosuppressive therapy, are risks for severe outcomes [54]. In terms of specific therapies, aside from glucocorticoids, receiving rituximab or sulfasalazine is associated with higher odds of death, compared to methotrexate monotherapy (OR 4.04, 95% CI 2.32-7.03) and (3.60, 1.66-7.78), respectively [54].…”
Section: What Lessons May Be Learned From Examining the Clinical Outcomes Of Patients On Immunomodulatory Therapy At Baseline?mentioning
confidence: 99%
“…21 Furthermore, among 390 (10%) of 3729 patients who had died as of July 1, 2020, a prednisolone equivalent of more than 10 mg daily was found to be associated with death (OR 1•69, 95% CI 1•18-2•41). 22 At a population level, glucocorticoid therapy was also associated with an increased risk of hospitalisation and mortality. 2 Of course, observational studies have many limitations, most notably confounding by indication, and current modelling does not have the power to fully adjust for severity of the underlying rheumatic disease in patients treated with glucocorticoids.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…By contrast, the chronic use of maintenance doses of glucocorticoids (eg, prednisolone ≥10 mg daily) seems to be associated with an increased risk of COVID-19-related hospitalisation and mortality. 2,21,22 Therefore, the value of glucocorticoids in COVID-19 might relate to the stage of disease, and these drugs might be more effective once the immune response overtakes the viral replication stage as the major driver of symptoms and complications. Since dexamethasone has minimal mineralocorticoid effects, it might be that the glucocorticoid effect exerts much of the benefit.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Response to: 'Correspondence on 'Factors associated with COVID-19-related death in people with rheumatic diseases: results from the COVID-19 Global Rheumatology Alliance physician reported registry' by Arnaud and Devilliers We thank Arnaud and Devilliers 1 for their correspondence on our article. 2 They raise the important topic of risk prediction models for estimating the risk of COVID-19-related death, and the potential development of a risk prediction tool using data from our article.…”
mentioning
confidence: 98%